Sst = ssw + ssb
I have this problem to solve. It's been a while since I tried to figured out how to do, but I am totally lost.
Here it is.
Prove SST= SSW+SST in one-way Anova (one factor).
Σ ( xi - x̄ )² = Σ (xi - x̄ + x̄ k - x̄ k ) ²
Hint: Σ [ ( xi - x̄ k ) + ( x̄ k - x̄ )]²
Where should I start? Should I try to compute Σ [ ( xi - x̄ k ) + ( x̄ k - x̄ )]² in order to come up with SST= Σ ( xi - x̄ )²
Seriously, I have no idea ...
Any help ? (Crying)
Re: Sst = ssw + ssb
What is SSW and SST again? (In terms of the symbols you are using? Also note that Var[X+Y] = Var[X] + Var[Y] if X and Y are independent quantities (random variables, samples, etc).